2012
DOI: 10.1074/jbc.m111.304006
|View full text |Cite|
|
Sign up to set email alerts
|

Oncogenic Ras and B-Raf Proteins Positively Regulate Death Receptor 5 Expression through Co-activation of ERK and JNK Signaling

Abstract: Background:The oncogene Ras induces DR5 expression with undefined mechanism. Results: Both Ras and B-Raf induce DR5 expression through co-activation of ERK and JNK signaling and subsequent cooperative effects among CHOP, Elk1, and c-Jun. Conclusion: Co-activation of ERK and JNK signaling accounts for Ras-induced DR5 expression. Significance: A novel function of DR5 in Ras-or B-Raf-mediated oncogenesis may be suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 51 publications
7
41
0
Order By: Relevance
“…2). Vemurafenib reduced DR5 levels in SK-Mel19 cells, in agreement with previous studies [26](Supplemental Fig. 3A).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…2). Vemurafenib reduced DR5 levels in SK-Mel19 cells, in agreement with previous studies [26](Supplemental Fig. 3A).…”
Section: Resultssupporting
confidence: 93%
“…We noted caspase 8 activation and PARP cleavage after long-term BRAF inhibition, preceded by up-regulation of FAS, but down-regulation of DR5, in agreement with other studies of DR5 regulation by activated RAS/RAF [26]. We noted suppression of FAS levels by expression of activated BRAF, which was relieved following treatment with vemurafenib.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have suggested that PKCd activates ERK dependently of Raf (34). Recent studies have shown that Ras and B-Raf induce DR5 expression in an ERK/RSK2-dependent manner (35). So, it is necessary to investigate whether PKCd regulates ERK/RSK2 expression through activation of Ras and Raf.…”
Section: Discussionmentioning
confidence: 99%
“…A striking high expression of phosphorylated MEK and ERK was found in ALDH1 + NSCLC cells. Previous studies have shown that DR5 and DR4 expression is positively regulated by MEK/ERK signaling [25][26][27].…”
Section: Discussionmentioning
confidence: 99%